PENGEMBANGAN INDIKATOR 4 C’s YANG SELARAS DENGAN KURIKULUM 2013 PADA MATA PELAJARAN MATEMATIKA SMP/MTs KELAS VII SEMESTER 1 - Sari, Diah Ayu Nurvita; Sunardi, S; Kurniati, Dian (Kadikma, 2018)
Abstract. The purpose of this research is to describe process and development result of 4 C's indicators that aligned with curriculum 2013 on the first semester mathematics subject of seventh grade junior high school. 4 C's indicators are indicator of ability that exist in P21 which consist of critical thinking, creative, collaboration and communication. Research type which is used in modified Plomp's development model. Plomp's development phases consists of 4 phase which are, (1) initial investigation phase; (2) designing phase; (3) realisation/ construction phase; (4) test, evaluation, and revision phase. The developed learning materials consist of the number patterns; Cartesian field; Relations and functions; Equation of straight line and sisterm of two linear equations. The development is done by making the 4 C's indicator that aligned with the curriculum 2013. The data collection process is done through product validity test which has been developed by several lecturers and teachers. Validation results were analyzed to conclude that the 4 C's indicator developed was valid after a revision based on the suggestion of some experts with validity criteria greater than or equal to 3.20. Keyword: Plomp's development model, 4 C's indicators, Curriculum 2013